Practical Considerations in the Conduct of Micronucleus Test - Rao, K. Suryanarayana (Biology, Engineering, Medicine and Science Reports)
Genotoxicity is commonly evaluated during the chemical safety assessment together with other toxicological endpoints. The micronucleus test is always included in many genotoxicity test guidelines for long time in many classes of chemicals, e.g., pharmaceutical chemicals, agricultural chemicals, food additives. Although the trend of the safety assessment of chemicals faces to animal welfare and in vitro systems are more welcome than the in vivo systems, the in vivo test systems are paid more attention in the field of genotoxicity because of its weight of evidence. Chromosome defects are recognized as being the basis of a number of human genetic diseases. Chemicals can be tested in vitro for their ability to produce chromosome aberrations in cells with which they have direct contact in a static system. Chemicals may react differently in vivo, however, where metabolic systems other than liver cytochrome P448/P450 operate, and where the dynamic processes of absorption, metabolism and excretion are involved. Chemicals should therefore also be tested for chromosome damaging activity in vivo.